EVALUASI SINKRONISASI PERENCANAAN DAN PENGANGGARAN BIDANG PERUMAHAN DAN PERMUKIMAN PADA PEMERINTAH PUSAT - Dwi Resti Pratiwi (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
Aligning national planning and budgeting are crucial to achieving national development’s goals. One of Indonesia development goals as stated on Mid- Termn National Development Planning (RPJMN) 2015-2019 was to reduce poverty at 7-8 percent by the end of 2019. This target however is hard to be reached. It is indicated that there was a problem on planning and budgeting system at program priority and activity level. One of program priority that was mandated to achieve poverty target is housing and settlement. The outcome of the program unfortunately were unreachable. They were to reduce the housing backlog by 5 million unit and universal access to water supply and sanitation by 2019. This paper aims to evaluate the national planning budgeting alignment on Housing and Settlement Program. It used descriptive analysis methode by comparing between planning document such as RPJMN, Government Strategic Plan (Renstra), Government Work Plan (RKP) and Budget States (APBN). This analysis resulted that there is inconsistency outcome indicators across planning document (i.e RPJMN and RKP). Beside that, the missmatch between planning and budget document is found in this housing and settlement program which cause many activities were not funded in APBN. So that, the next government should evaluate the implementation of planning and budgeting during 2015-2019 and improve the alignment between them to achieve naional development goals as stated in RPJMN 2020-2024.